Bakhtinian Carnivalesque and Gender Erasure in Ziggy Zezsyazeoviennazabrizkie’s Kering: Collective Child Voices and Communal Space - Pitaloka, Diah; Atikurrahman, Moh; Siregar, Wahidah Zein Br (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
This article examines how Ziggy Zezsyazeoviennazabrizkie’s short story Kering constructs an alternative social world through the erasure of gender legibility, the centering of child characters, and the laundromat as a communal refuge. This study asks: (1) how the laundromat operates as a carnivalesque liminal chronotope; (2) how the collective first-person plural voice generates polyphony and shared child subjectivity; and (3) how voicelessness and bodily/identity anomalies mobilize grotesque realism to critique gendered structural violence. This research employs qualitative close reading supported by directed coding based on Bakhtinian carnivalesque theory (carnival “second life,” degradation/uncrowning, grotesque realism) and a gender-inclusive narrative perspective. Textual segments are coded across three analytic axes (space, voice, and body) then synthesized through interpretive content analysis. Kering stages the laundromat as a temporary egalitarian commons that suspends adult/patriarchal authority, enabling children’s communal life. The collective “we” voice distributes narrative agency across multiple child figures, producing polyphonic witnessing while weakening gender as a stable organizing category. Grotesque bodily imagery and motifs of voicelessness translate unspeakable harm into a material critique of structural violence, positioning gender erasure as a deliberate oppositional strategy rather than neutrality. The analysis focuses on a single short story; broader claims require comparative studies across contemporary Indonesian fiction and reader-reception research. The article integrates Bakhtinian carnivalesque, collective narration, and gender-inclusive reading to reframe children as modern subjects who contest normative gender and violence through form.